Effect of apricot kernel seed extract on biophysical properties of chitosan film for packaging applications - Mona Saied; Azza Ward; Shimaa Farag Hamieda (Scientific Reports, 2024)
Abstract Chitosan is a natural biodegradable biopolymer that has drawbacks in mechanical and antibacterial properties, limiting its usage in biological and medicinal fields. Chitosan is combined with other naturally occurring substances possessing biological antibacterial qualities in order to broaden its application. Ethanolic apricot kernel seed extract was prepared, analyzed, and incorporated into chitosan film with different concentrations (0.25, 0.5, and 0.75 wt%). Furthermore, the effect of AKSE and γ-radiation (20 Gy and 20 kGy) on the physical properties of the film was studied. The prepared films were characterized by Fourier transform infrared spectroscopy (FTIR), which revealed that AKSE did not cause any change in the molecular structure, whereas the γ-irradiation dose caused a decrease in the peak intensity of all concentrations except 0.75 wt%, which was the most resistant. In addition, their dielectric, optical, and antimicrobial properties were studied. Also, AKSE-enhanced optical qualities, allowed them to fully block light transmission at wavelengths of 450–600 nm. The dielectric properties, i.e., permittivity (ε′), dielectric loss (ε′′), and electrical conductivity (σ), increased with increasing AKSE concentration and film irradiation. The antimicrobial studies revealed that the antimicrobial activity against Escherichia coli and Canodida albicans increased with AKSE incorporation.